2021
DOI: 10.1111/pai.13685
|View full text |Cite
|
Sign up to set email alerts
|

Changing pattern of pediatric anaphylaxis in Hong Kong, 2010–2019

Abstract: Background Anaphylaxis is a significant health burden in most Western countries, but there are little published data on the incidence and pattern of anaphylaxis in Asia. We aim to determine the incidence rate and pattern of anaphylaxis over the past decade among the pediatric population in Hong Kong. Methods Medical records of patients presenting with allergy‐related symptoms during the period 2010 to 2019 were examined. Pediatric patients aged below 18 years who fulfilled the diagnostic criteria for anaphylax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Since Hong Kong is a westernized city, we believed the same situation is happening here 4,28–30 . This finding is comparable to recent research on pediatric anaphylaxis patterns, that food triggers such as milk and eggs are predominantly seen in the age group from birth to 4 years, while shellfish is the highest allergen trigger, usually at a later age factor 6 …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Since Hong Kong is a westernized city, we believed the same situation is happening here 4,28–30 . This finding is comparable to recent research on pediatric anaphylaxis patterns, that food triggers such as milk and eggs are predominantly seen in the age group from birth to 4 years, while shellfish is the highest allergen trigger, usually at a later age factor 6 …”
Section: Discussionsupporting
confidence: 88%
“…4,[28][29][30] This finding is comparable to recent research on pediatric anaphylaxis patterns, that food triggers such as milk and eggs are predominantly seen in the age group from birth to 4 years, while shellfish is the highest allergen trigger, usually at a later age factor. 6 Furthermore, CFA helps to make sure that the components are measuring what they are supposed to but the goodness-of-fit statistics of CFA in this study showed a poor fit for the domains of all questionnaires. Therefore, exploratory factor analysis was done and the categories of items entered different domains.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Although shellfish allergy is more common in adults, it affects also 1.3% of children in the US as compared to the estimated prevalence of peanut allergy ranging from 1.2–2.2% [1 ▪ ,2 ▪ ]. Shellfish is also the predominant food eliciting anaphylactic reactions affecting 43.8% of the pediatric population between 15 and 17 years old [3 ▪ ]. Patients suffering from shellfish allergy can develop mouth and throat itching, lip swelling and skin reactions such as urticaria, periorbital angioedema and skin redness.…”
Section: Introductionmentioning
confidence: 99%
“…Our territory-wide survey revealed that fish was a main cause of adverse food reactions in Hong Kong pre-school children 3 . Collectively, fish was also a major food triggers of pediatric anaphylaxis, which affected a wide range of children from infants to school-age children in Hong Kong 4 . It is therefore important to identify the spectrum of fish allergen in order to design optimal diagnostic approach and design immunotherapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%